Digital Marketing of Maggot Cultivation Products in Cepogo Village, Boyolali through Website Development and E-Commerce Integration - Hariyadi Fajar Nugroho; Fatih Kurniawan; Anung Damar Sasongko (JARDIRA – Jurnal Pengabdian Digital dan Rekayasa Informatika, 2026)
Background: The maggot cultivation group in Cepogo Village, Boyolali has economic and ecological potential, but product marketing remains conventional and lacks an integrated digital medium. Contribution: This program strengthens partner capacity by developing a website-based and e-commerce-oriented promotion model for maggot products. Method: The activity was implemented through needs observation, website design, product catalog development, WhatsApp Business and marketplace integration, training, and evaluation. Results: The outputs include a marketing website design, a digital product catalog, an online ordering flow, an admin dashboard concept, and activity documentation. Conclusion: Digital marketing helps organize product information, strengthen business identity, and facilitate online ordering access for potential customers.